Functional characterization of 3D contractile smooth muscle tissues generated using a unique microfluidic 3D bioprinting technology. Issue 1 (4th December 2019) - Dickman, Christopher T. D.; Russo, Valerio; Thain, Katherine; Pan, Sheng; Beyer, Simon T.; Walus, Konrad; Getsios, Spiro; Mohamed, Tamer; Wadsworth, Sam J.
Abstract: Conditions such as asthma and inflammatory bowel disease are characterized by aberrant smooth muscle contraction. It has proven difficult to develop human cell‐based models that mimic acute muscle contraction in 2D in vitro cultures due to the nonphysiological chemical and mechanical properties of lab plastics that do not allow for muscle cell contraction. To enhance the relevance of in vitro models for human disease, we describe how functional 3D smooth muscle tissue that exhibits physiological and pharmacologically relevant acute contraction and relaxation responses can be reproducibly fabricated using a unique microfluidic 3D bioprinting technology. Primary human airway and intestinal smooth muscle cells were printed into rings of muscle tissue at high density and viability. Printed tissues contracted to physiological concentrations of histamine (0.01‐100 μM) and relaxed to salbutamol, a pharmacological compound used to relieve asthmatic exacerbations. The addition of TGFβ to airway muscle rings induced an increase in unstimulated muscle shortening and a decreased response to salbutamol, a phenomenon which also occurs in chronic lung diseases. Results indicate that the 3D bioprinted smooth muscle is a physiologically relevant in vitro model that can be utilized to study disease pathways and the effects of novel therapeutics on acute contraction and chronic tissue stenosis.